Comparative analysis of the reps number within two training macrocycles of the weightlifting Olympic team - Ulareanu, M. V.; Potop, V. (Journal of Physical Education and Sport, 2010)
The authors present a comparative analysis of the number of repetitions in two training macro-cycles of the weightlifting Olympic team. We have considered that the differences between the number of reps in each training stage of the macro-cycles no. 1 and 2 will influence the performances achieved in competition. This approach has led to the organization of a study group in the weightlifting Olympic team of Romania. The scientific argument is the presentation of the number of reps during the preparation of the weightlifting Olympic team in different mezzo and micro-cycles of training, that, by decreasing the number of reps and increasing the intensity of the effort up to the maximum level from a training micro-cycle to another, contributes to reaching the fitness peak in competitive period within the macro-cycle no.1; also, an optimum number of reps during the training macro-cycle no.2 will make possible to keep the fitness necessary for their turning into good account in the next competition. The study was conducted over a period of two training macro-cycles (04.01-16.08.2008), with a group of 6 athletes, of 17 to 31 years old, whose target of performance was the participation in the European Championships (E. C.) for Seniors, Lignano - Sabbiadoro, Italy 2008 and the Olympic Games (J.O.) in Beijing in 2008. The athletes` progresses during the training stages and competitions were recorded by means of the statistical-mathematical and plotting methods. The study highlights the number of reps within two training macro-cycles of the weightlifting Olympic team. At the end of the paper we are able to confirm that the differences between the number of reps at each stage of training in the macro-cycles no. 1 and 2 have influenced the performances achieved in competition.